Evaluation of small ncRNAs as a possible epigenetic mechanism mediating the hemibiotrophic transition in the life cycle of Phytophthora infestans (2017)
Phytophthora infestans, the causal agent of late blight disease, is responsible for worldwide billionaire losses each year. This plant pathogenic oomycete is a hemibiotroph, meaning that in the early stages of infection it feeds on living host tissue and later in the infection cycle, it kills the host. Even though transcription dynamics of the transition from biotroph to necrotroph are well characterized, whether if its regulation occurs mainly by small non-coding RNAs (ncRNAs) is not. Thus, the aim of this study was to investigate whether small ncRNAs can constitute an epigenetic regulatory mechanism for the hemibiotrophic transition in P. infestans. RNAseq data of different life cycle stages of P. infestans was obtained from available web repositories. It was analyzed by searching for ncRNAs that presented a statistically significant differential expression when comparing the different stages of the transition...